2012
DOI: 10.1002/ejic.201200334
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Effect on Perrhenate Recognition by Polyammonium Cages

Abstract: The affinity of azacryptands towards perrhenate has been investigated by potentiometric, 1 H NMR spectroscopic and ITC studies in aqueous solutions. The association constants could only be determined for the p-xylyl and m-xylyl azacryptands in the hexaprotonated form. The experimental results showed the outstanding affinity of the p-xylyl cryptand for perrhenate, attributable to the geometric complementarity between the anion and the cavity of the receptor. Single crystals of the inclusion complex could also b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
5
30
0
Order By: Relevance
“…19 shows the distribution diagram of the species present at the equilibrium over the 2-12 pH interval, (0.1 M NaCF 3 SO 3 , T = 25°C), in the case of bistren cryptand 7. 34 The diagram in Fig. 19 shows that at pH 2 100% LH 6 6+ is present .…”
Section: Anion Receptors Derived By the Protonation Of Bistren Cryptandsmentioning
confidence: 96%
“…19 shows the distribution diagram of the species present at the equilibrium over the 2-12 pH interval, (0.1 M NaCF 3 SO 3 , T = 25°C), in the case of bistren cryptand 7. 34 The diagram in Fig. 19 shows that at pH 2 100% LH 6 6+ is present .…”
Section: Anion Receptors Derived By the Protonation Of Bistren Cryptandsmentioning
confidence: 96%
“…Steps forward on 99 TcO 4 − recognition were made by Sessler, Katayev, and coworkers, although again not in aqueous solution 9–11. Recently, our group investigated the binding propensities of poly‐protonated azacryptands towards ReO 4 − in water 12. These studies revealed the receptor LH 6 6+ to have the most suitable cavity for incorporation of the anion.…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed the receptor LH 6 6+ to have the most suitable cavity for incorporation of the anion. The selectivity of LH 6 6+ for ReO 4 − was demonstrated by comparing the affinity constant with those obtained with several other anions (such as chloride and nitrate) 12…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, some supramolecular hosts have been designed to bind perrhenate in a very selective manner, however, their operations are limited to organic media or organic/aqueous mixtures . To overcome this limitation, recently, some supramolecular receptors have been synthesized that utilize a combination of electrostatic interactions and multiple hydrogen‐bonding interactions and, more recently, halogen bonding to achieve the selective binding of the perrhenate anion in aqueous media . To exploit the selective binding of the designed supramolecular host with the perrhenate/pertechnetate anion for its analytical detection, one such receptor molecule was functionalized with a fluorophore, anthracene, which signaled the binding of the perrhenate/pertechnetate to the receptor molecule through a decrease in its fluorescence intensity .…”
Section: Introductionmentioning
confidence: 99%